Idempotence Is Not a Medical Condition. (Communications of the ACM, 2012)
The article focuses on messaging in distributed computing environments and the development of idempotent software applications. It states idempotence is essential for reliable systems and is a mathematical term that means operations will have the same effect every time it is performed. It mentions that most applications include messaging with multiple partners utilizing semi-stable Internet standards which support the evolving environment but are unable to eliminate some anomalies. It comments on the effect TCP has had on data communication for use in communicating processes and uses HTTP Web requests as an example of an idempotent process.